Dynamic Spacer Installation for Multirole Metal–Organic Frameworks: A New Direction toward Multifunctional MOFs Achieving Ultrahigh Methane Storage Working Capacity - Chen, Cheng-Xia; Wei, Zhang-Wen; Jiang, Ji-Jun; Zheng, Shao-Ping; Wang, Hai-Ping; Qiu, Qian-Feng; Cao, Chen-Chen; Fenske, Dieter; Su, Cheng-Yong (Journal of the American Chemical Society, 2017)
A robust Zr-MOF (LIFM-28) containing replaceable coordination sites for additional spacer installation has been employed to demonstrate a swing- or multirole strategy for multifunctional MOFs. Through reversible installation/uninstallation of two types of spacers with different lengths and variable functional groups, different tasks can be accomplished using the same parent MOF. An orthogonal optimizing method is applied with seven shorter (L1–7) and six longer (L8–13) spacers to tune the functionalities, achieving multipurpose switches among gas separation, catalysis, click reaction, luminescence, and particularly, ultrahigh methane storage working capacity at 5–80 bar and 298 K.